Vector radiative transfer code SORD: Performance analysis and quick start guide. (October 2017) - Korkin, Sergey; Lyapustin, Alexei; Sinyuk, Alexander; Holben, Brent; Kokhanovsky, Alexander
Highlights: We present detailed accuracy and runtime analysis for the newly developed vector radiative transfer code against 52 benchmarks Degree of linear polarization converges faster than the total intensity There is a lack of published accurate benchmarks for RT in atmosphere over anisotropic polarized land reflection models and over ocean reflection models with specified wind direction Efficiency of the linear-exponential fit for vertical numerical integration in the method of successive orders is disputable and needs further analysis. Abstract: We present a new open source polarized radiative transfer code SORD written in Fortran 90/95. SORD numerically simulates propagation of monochromatic solar radiation in a plane-parallel atmosphere over a reflecting surface using the method of successive orders of scattering (hence the name). Thermal emission is ignored. We did not improve the method in any way, but report the accuracy and runtime in 52 benchmark scenarios. This paper also serves as a quick start user's guide for the code available fromftp://maiac.gsfc.nasa.gov/pub/skorkin, from the JQSRT website, or from the corresponding (first) author.